Blunt Abdominal Trauma, Splenectomy, and Post-Splenectomy Vaccination. (5th September 2018) - Stockinger, Zsolt; Grabo, Daniel; Benov, Avi; Tien, Homer; Seery, Jason; Humphries, Ashley
Abstract: Unlike penetrating abdominal injuries where the decision to operate is relatively straight forward, those combat casualties that sustain blunt abdominal trauma offer more of a diagnostic and clinical challenge. For unstable patients with a positive focused abdominal sonography in trauma or diagnostic peritoneal lavage, exploratory laparotomy should be undertaken immediately. All grade IV–V splenic injuries should undergo splenectomy, patients undergoing attempted splenic salvage should be monitored in the Role 3 facility and embolization of such splenic injuries may be considered if available. Patients who fail non-operative management of the spleen require splenectomy at the Role 3 prior to aeromedical evacuation. Overwhelming post-splenectomy infection is a serious disease that can progress from a mild flu-like illness to fulminant sepsis in a short period of time. Although relatively rare, it has a high mortality rate with delayed or inadequate treatment. All splenectomized patients and those deemed to be functionally asplenic should be vaccinated within 14 days from splenectomy and prior to aeromedical evacuation.